ANALISIS PERBEDAAN KADAR NITRIT SUMUR GALI TPA DENGAN PENAMBAHAN DAN TANPA Na2EDTA - Yahya Wiranatanegara; Ian Kurniawan; Pra Dian Mariadi (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
The nitrite-in-water examination should be noted for the existence of the iron metalcation (Fe+), in the water cation samples can affect the test result of nitrite levels at thetime of reading in the UV-Vis spectrophotometer. Na2EDTA Additions function to bindthe metal found in the sample as well as chemical disorders as in the presence ofchemical formation that can lead to not perfecting the association of substances to beanalyzed so as to influence measurements at the time of reading in Spectrophotometer.The nitrite rate assessment was measured using the UV-Vis spectrophotometer methodwith a wavelength of 534 nm. The measuring rate range is 0.01 mg/L to 1.00 mg/L. Thereare differences in nitrite-level test results on well-dug water around the TPA withaddition and without Na2EDTA using Uv-vis spectrophotometry.